Os gauleses em César, Tito Lívio e Plínio, o Velho: sobre a retórica de representação do outro e a construção de si - Priscilla Adriane Ferreira Almeida (2018)
We know th t the G uls didnt le ve ny written m teri l nd their culture nd history are known today by third-part reports and by archeological studies. Therefore, the theme of G uls represent tions in C es r, Livy nd Pliny the Elder, s it comprehends the temporal period from the I Century B.C. to I A.C., is the main objective of this academic paper, as it coincides with the moment in wich Gaul was conquered and transformed into a Roman province. In the beginning of this paper we offer a reflection about the word b rb ri n itself; besides we focus on the concept of barbarity and civilization among Greeks nd Rom ns There fter we t lk bout the exp nsion of Romes dom in nd how w s the contact between Romans and Gauls. In addition we put forward to research some Latin passages about the Gauls, and the sources are: De bello Gallico (The Gallic War), of Caesar, Ab urbe condita (The History of Rome), of Livy, and in the Historia naturalis (Natural History), of Pliny, the Elder. In this analysis of the Latin passages we will be ble to re lize how the rhetoric of G uls represent tions is structured nd how the construction of the image of the barbarian worked. We will also make some considerations about what was by the Romans from the I Century B.C. to I A.C. considered as barbarian (or civilized). Furthermore we make a research of the rhetoric elements used by Caesar, Livy and Pliny to distinguish the Gauls, as well to analyze the type of vocabulary and representative figures applied in these descriptions. Finally we close this academic paper by bringing some facts of what is know today by the Gauls through historiographical and archeological researches.